EFFECT OF CURRENT, PULSE DURATION, AND PULSE INTERVAL FOR DIFFERENT ELECTRODES SHAPE ON ELECTRODE WEAR RATE IN EDM - Nagham Ghanem Ghazey and Dr. Shukry Hammed Aghdeab (International Journal of Research Science and Management, 2017)
The process of electrical discharge machining (EDM) includes thermal erosion of the workpiece by a series of sparks from an electrode depending on electrical source of energy. The workpiece and the electrode are submerged in a dielectric fluid. This paper presents an experimental investigation for studying the effect of electrodes shape using (flat, conical, and round) bottoms, currents of (10, 20, and 42 A), pulse duration of (25, 50, and 75 µs) and pulse interval of (37, 12, and 3.5 µs) on electrode wear rate (EWR). A series of experiments was carried out using 27 specimens, workpiece of AISI 1060 steel material with thickness of 2 mm, electrode of extra high leaded brass material with diameter of 16 mm, and transformer oil as dielectric liquid. The relationship between machining parameters (current, pulse duration, and pulse interval) and electrode wear rate (EWR) was found for each electrode shape and a comparison between electrodes shape was done to know which electrode shape gives lowest EWR. From experimented results, it is revealed that for most of runs conical electrode gives lowest EWR as compared with flat and round electrodes. The factorial design was used to develop a mathematical model to create a plot that shows the effect of electrodes shape and predict the values of EWR by the Minitab statistical software (MSS).